3-D structured SnO2–polypyrrole nanotubes applied in Na-ion batteries. Issue 105 (31st October 2016) - Ruan, Boyang; Guo, Haipeng; Liu, Qiannan; Shi, Dongqi; Chou, Shulei; Liu, Huakun; Chen, Guohua; Wang, Jiazhao
Abstract : SnO2 -coated polypyrrole (PPy) with a three-dimensional (3-D) structured nanotube network has been prepared via a facile hydrothermal method and tested as an anode material for Na-ion batteries. Abstract : SnO2 -coated polypyrrole (PPy) with a three-dimensional (3-D) structured nanotube network has been prepared via a facile hydrothermal method and tested as an anode material for Na-ion batteries. The crystalline SnO2 nanoparticles (less than 25 nm in size) are distributed uniformly on the surfaces of the PPy tubes. When it is used as an anode material for sodium-ion batteries (SIBs), the composite electrode can deliver a good reversible capacity of nearly 288 mA h g −1 when discharging at 100 mA g −1, with more than 69.1% capacity retention and stable coulombic efficiency of 99.6% after 150 cycles. The good electrochemical performance compared to the 151 mA h g −1 achieved by bare SnO2, which was fabricated by the same method in the absence of PPy, could be mainly attributed to the good dispersion of SnO2 on the 3-D matrix of PPy tubes, which facilitates the diffusion of Na + ions and buffers the large volumetric changes during charge/discharge. Our results suggest that such SnO2 /carbonaceous composites would be good anode candidates for SIBs.